EXO1 overexpression is associated with poor prognosis of hepatocellular carcinoma patients. Issue 19 (18th October 2018) - Dai, Yaoyao; Tang, Zuxiong; Yang, Zongguo; Zhang, Lan; Deng, Qing; Zhang, Xiaofeng; Yu, Yongchun; Liu, Xing; Zhu, Junfeng
ABSTRACT: The roles of exonuclease 1 (EXO1) in hepatocellular carcinoma (HCC) tumorigenesis and progression remain unclear. This study aimed to assess the prognostic value and therapeutic potential of EXO1 in HCC. Exo1 gene copy numbers were obtained from three Oncomine microarray datasets (n = 447). EXO1 mRNA expression was validated by semi-quantitative PCR and QuantiGene® 2.0 assays. Cell growth curve and colony formation were performed to asses the cell proliferation. Clonogenic assay, flow cytometry, and immunofluorescence were adopted to acess the effects of EXO1 knockdown and radiation on cell survival, cell cycle distribution and DNA repair. Western blots were performed to reveal the related mechanism. A significant copy number variation (CNV) of the Exo1 gene was found in HCC specimens in three separate sets of published microarray data. In the 143 cases treated by our team, EXO1 expression levels were elevated (86.71%, 124/143). In addition, EXO1 overexpression was correlated with larger tumor size ( P = 0.002), increased lymph node metastasis ( P =0.033) and lower Edmondson grade ( P = 0.018). High EXO1 expression unfavorably affected overall survival (OS) ( P = 0.009). Both univariate and multivariate Cox regression analyses identified EXO1 as an independent predictor of OS (univariate, P = 0.012; multivariate, P = 0.039). Silencing of EXO1 in vitro reduced cell proliferation. EXO1 knockdown further suppressed clonogenic cell survival, abrogated radiation-induced G2/M phase arrest, and enhanced γ-H2AX foci after exposure to irradiation. The accumulation of ataxiatelangiectasia mutated (ATM) might partially regulate the EXO1 related radiosensitivity. In summary, EXO1 could be a promising prognostic marker, with a potential therapeutic value in HCC.